La Tertulia: A Dialogic Model of Adult Basic Education in the New Information Age - Lidia ` Puigvert; Tere Sorde; Marta Soler (Adult Education Research Conference, 2000)
In the new information age dialogue and dialogic projects are increasingly becoming a social requirement. La Tertulia Literaria is a learning experience in which adults with non-academic background read Joyce, among other classics, crossing cultural barriers and transforming the horizons of their lives and environments.